Increased plasma FGF21 level as an early biomarker for insulin resistance and metabolic disturbance in obese insulin-resistant rats - Pongpan Tanajak (2018)
© 2018, © The Author(s) 2018. Propose: To investigate the temporal relationship between plasma fibroblast growth factor 21 levels, insulin resistance, metabolic dysfunction and cardiac fibroblast growth factor 21 resistance in long-term high-fat diet–induced obese rats. Methods: In total, 36 male Wistar rats were fed with either a normal diet or high-fat diet for 12 weeks. Blood was collected from the tail tip, and plasma was used to determine metabolic profiles and fibroblast growth factor 21 levels. Rats were sacrificed at weeks 4, 8 and 12, and the hearts were rapidly removed for the determination of cardiac fibroblast growth factor 21 signalling pathways. Results: Body weight and plasma fibroblast growth factor 21 levels were increased after 4 weeks of consumption of a high-fat diet. At weeks 8 and 12, high-fat diet rats had significantly increased body weight and plasma fibroblast growth factor 21 levels, together with increased plasma insulin, HOMA index, area under the curve of glucose, plasma total cholesterol, plasma low-density lipoprotein cholesterol, serum malondialdehyde and cardiac malondialdehyde levels. However, plasma high-density lipoprotein cholesterol levels and cardiac fibroblast growth factor 21 signalling proteins (p-FGFR1 Tyr154, p-ERK1/2 Thr202/Tyr204and p-Akt Ser473) were decreased, compared with normal diet rats. Conclusion: These findings suggest that plasma fibroblast growth factor 21 levels could be an early predictive biomarker prior to the development of insulin resistance, metabolic disturbance and cardiac fibroblast growth factor 21 resistance.